2018
DOI: 10.1063/1.5066047
|View full text |Cite
|
Sign up to set email alerts
|

Alfvénic gap eigenmode in a linear plasma with ending magnetic throats

Abstract: To guide the experimental design of a linear plasma device for studying the interaction between energetic ions and Alfvénic gap eigenmode (AGE), this work computes AGE referring to fusion conditions in a ultra-long large plasma cylinder ended with strong magnetic throats for axial confinement of charged particles. It is shown that:(i) for uniform equilibrium field between the ending throats, the dispersion relation of computed wave field agrees well with a simple analytical model for shear Alfvénic mode; (ii) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 35 publications
2
2
0
Order By: Relevance
“…4, in terms of normalized wave magnetic field at z = 0 m and r = 0 m. It can be seen that the center and width of the spectral gap remain unchanged when the number increases, implying the evidence of no frequency shift. This is consistent with the previous observation that the gap eigenmode (discrete eigenmode inside the spectral gap) changes negligibly for various magnetic mirrors as long as the number is above a certain value [12,13,23]. Then the variation of the spectral gap with mirror depth is illustrated in fig.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…4, in terms of normalized wave magnetic field at z = 0 m and r = 0 m. It can be seen that the center and width of the spectral gap remain unchanged when the number increases, implying the evidence of no frequency shift. This is consistent with the previous observation that the gap eigenmode (discrete eigenmode inside the spectral gap) changes negligibly for various magnetic mirrors as long as the number is above a certain value [12,13,23]. Then the variation of the spectral gap with mirror depth is illustrated in fig.…”
supporting
confidence: 91%
“…The underlying physics of this downward frequency shift is unclear, although a simple theoretical analysis has been proposed. It may be similar to a flute-like effect for which the resonant frequency decreases as the air column becomes longer [23]. Realistic conditions on the LAPD, including the limited number (≤4.5) and depth (≤0.39) of periodic modulations and the mixed feature of kinetic and inertial plasma regions, are also discussed and we found that the computed spectral gap agrees well with the experimental data measured previously [10].…”
supporting
confidence: 83%
See 2 more Smart Citations